Driver Assistance System using in-vehicle Traffic Lights and Signs - Jain, Vaibhav; ., Tanay; Gangele, Saransh; Kalimuthu, K (International Journal of Engineering and Technology, 2018)
In recent years, with the advancement of vehicular communication, it is possible to detect various road signs and provide traffic light information to the driver inside the vehicle with the application of heads-up display (HUD). It detects road signs, does basic classifications and accordingly directs the driver to slow down or stop the vehicle. The vehicleâ€™s heads-up display keeps the driver focused by providing road warnings, speed limit, traffic signals and some vital navigation information in the driverâ€™s line of sight(LOS). This system has 4 phases, Image recognition, wireless communication, obstacle detection and driver mechanism. This system aims to create a prototype of a smart driver assistance system which provides better road traffic and driverâ€™s safety in countries with high traffic congestion where fully automated vehicles cannot function effectively. This system can be easily implemented in real time scenarios to reduce accidents and enhance the convenience of driving.Â